(untitled) (Al-Qamar, 2022)
In Idealism the representation of things in ideal or Idealized form. This concepts that “what is” insufficient and uncomplete and give importance to “what should be” this is the central point of literary idealism. It depends on only the activity of mind. It known as idealism holds that the foundation of reality is thoughts or ideas. Idealism is a philosophy that contends that only awareness or the contents of consciousness can be know, not anything’s in the outside world. Urdu short story holds special importance the concept of idealism. Short story has been passing through many changes time to time. Now a days modern short story is showing the dream of an ideal society in which there is no social injustice and economic exploitation.